Up Scaling of Sweet Potato Based Pig Feeding System in Hill Eco-System of Meghalaya- A Case Study - Baishya, S. K.; Ray, S. K.; Barua, U.; Bordoloi, R. M.; Rajkhowa, D. J.; Tripathi, A. K. (Indian Journal of Hill Farming, 2019)
The aim of the present study was to find out the efficacy of sweet potato based feeding system for pig in order to upscale and promotes in a hill eco-system of Meghalaya. The study was conducted at 16 villages covering 109 farmers under the front line demonstration programme of ICAR-Krishi Vigyan Kendra Ri-bhoi. Three promising sweet potato varieties viz. ST-14, Kokrajhar and Meghalaya local were introduced in the farmers’ field to feed 56 numbers of Hampshire cross-breed piglets of 2-3 months age. Piglets were grouped equally into group I and II. The group I was fed with sweat potato tuber and vines (50%) and concentrate feed (50%), and group II fed with local feeding practices. The results of the study revealed that out of the three varieties demonstrated ST-14 was found to be performing well with an average yield of 36 t/ha followed by Meghalaya local (31 t/ha) and Kokrajhar Red (22 t/ha). Significantly higher (p< 0.01) body weight gain was recorded in pigs fed with sweet potato based ration than with local feeding ration (32.05 ± 0.50 vs 23.45 ± 0.49 kg) at 6 months of age. In addition, the supplementation of sweet potato (50%) in the pig ration reduced about 65% of total concentrates feed cost. It could be concluded that sweet potato based pig ration could be an economically viable and potential feeding system for pig growers in the hilly ecosystem of Meghalaya.